Spotlight on Volasertib: Preclinical and Clinical Evaluation of a Promising Plk1 Inhibitor. Issue 4 (3rd May 2016) - Van den Bossche, J.; Lardon, F.; Deschoolmeester, V.; De Pauw, I.; Vermorken, J.B.; Specenier, P.; Pauwels, P.; Peeters, M.; Wouters, A.
Abstract: Considering the important side effects of conventional microtubule targeting agents, more and more research focuses on regulatory proteins for the development of mitosis‐specific agents. Polo‐like kinase 1 (Plk1), a master regulator of several cell cycle events, has arisen as an intriguing target in this research field. The observed overexpression of Plk1 in a broad range of human malignancies has given rise to the development of several potent and specific small molecule inhibitors targeting the kinase. In this review, we focus on volasertib (BI6727), the lead agent in category of Plk1 inhibitors at the moment. Numerous preclinical experiments have demonstrated that BI6727 is highly active across a variety of carcinoma cell lines, and the inhibitor has been reported to induce tumor regression in several xenograft models. Moreover, volasertib has shown clinical efficacy in multiple tumor types. As a result, Food and Drug Administration (FDA) has recently awarded volasertib the Breakthrough Therapy status after significant benefit was observed in acute myeloid leukemia (AML) patients treated with the Plk1 inhibitor. Here, we discuss both preclinical and clinical data available for volasertib administered as monotherapy or in combination with other anticancer therapies in a broad range of tumor types.